Antioxidant, anti-inflammatory, and antiproliferative activities of Flourensia spp. - Jasso de Rodríguez, Diana; Torres-Moreno, Heriberto; López-Romero, Julio César; Vidal-Gutiérrez, Max; Villarreal-Quintanilla, José Ángel; Carrillo-Lomelí, Dennise Anahí; Robles-Zepeda, Ramón Enrique; Vilegas, Wagner [UNESP] (Elsevier, 2023)
Lung cancer originates from inflammatory processes mediated by pro-inflammatory cytokines, such as tumor necrosis factor-alpha (TNF-α) or molecular markers, such as nitric oxide (NO). Flourensia cernua, F. retinophylla, and F. microphylla have been studied and shown to possess remarkable antioxidant and biological activities. Therefore, the present study aimed to determine the total phenolic content (TPC), antioxidant capacity, and chemical composition of F. cernua, F. retinophylla, and F. microphylla extracts, as well as its anti-inflammatory activities in vitro on RAW 264.7 macrophages cells. Further, the cytotoxic and antiproliferative activities in vitro were assessed using A549 lung cancer cells and ARPE-19 cells. The TPC were assessed by the Folin-Ciocalteu method; antioxidant activity was assessed using the ABTS, DPPH, and FRAP techniques, and the chemical composition was determined by ESI-IT-MSn. The cytotoxic and antiproliferative properties were measured using the MTT assay. The anti-inflammatory activity was determined by evaluating the inhibition of NO and TNF-α production. The results showed that F. microphylla presented the highest TPC value of 284.83 mg GAE/g DW, and antioxidant activity with values of 20.4 μg TE/mL, 6.7 μg TE/mL, 3122.9 μM Fe(II)/g DW for DPPH, ABTS, and FRAP assays, respectively. A total of nine, five, and nine chemical compounds were identified in F. cernua, F. retinophylla, and F. microphylla, respectively. Moreover, the three extracts evaluated presented antiproliferative effect on A549 cells, and F. cernua demonstrated the best anti-inflammatory activity. Therefore, these extracts could be used as natural anti-inflammatory agents to control lung cancer.
Keywords: Anti-inflammatory; Flourensia spp.; Lung cancer; Nitric oxide; Polyphenolic compounds; Tumor necrosis factor-alpha